2019
DOI: 10.1007/jhep04(2019)115
|View full text |Cite
|
Sign up to set email alerts
|

A structural test for the conformal invariance of the critical 3d Ising model

Abstract: How can a renormalization group fixed point be scale invariant without being conformal? Polchinski (1988) showed that this may happen if the theory contains a virial current -a non-conserved vector operator of dimension exactly (d − 1), whose divergence expresses the trace of the stress tensor. We point out that this scenario can be probed via lattice Monte Carlo simulations, using the critical 3d Ising model as an example. Our results put a lower bound ∆ V > 5.0 on the scaling dimension of the lowest virial c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The version with general (m, n) will be important for the larger correlator system that puts Tµν on the same footing as σ, and χ 20. While these operators have never been accessed by the numerical bootstrap, results about Z2-even vectors in Monte Carlo simulations recently appeared in[90].…”
mentioning
confidence: 99%
“…The version with general (m, n) will be important for the larger correlator system that puts Tµν on the same footing as σ, and χ 20. While these operators have never been accessed by the numerical bootstrap, results about Z2-even vectors in Monte Carlo simulations recently appeared in[90].…”
mentioning
confidence: 99%
“…Non-unitary CFTs can arise for other values of N , such as N = 0, which describes self-avoiding random walks 5. The possibility that the critical theory is scale-, but not conformal, invariant has been recently excluded for the d = 3 φ 4 theory[16].…”
mentioning
confidence: 99%
“…(54)) is not valid anymore. This observation is at the heart of the criticism raised in in the recent preprint [30] where it was observed that, for N = 2, one can construct the conserved current J µ = ϕ 1 ∂ µ ϕ 2 − ϕ 2 ∂ µ ϕ 1 which is SO(2) invariant and has scaling dimension exactly equal to d − 1. At first sight this would be a counter-example of the present proof.…”
Section: Extension Of the Proof For Some O(n ) Modelsmentioning
confidence: 98%
“…Accordingly, in this important universality class, scale invariance implies conformal invariance in all dimensions. This proof has been criticized in [30] where it was argued that the assumptions made may not be fulfilled. Some elements of reply have already been presented in [31] but we discuss below in detail the issues raised in [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation